RETRACTED: Zero net energy building design as the way to increase the energy security of Armenia - Egnatosyan Siranush; Avetisyan Artur; Khachikyan Sos (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001